DECONSTRUCTING THE SUPPLY AND DEMAND MODEL IN THE PLATFORM ECONOMY ERA: A THEORETICAL REVIEW - Maureen Joanna Finny (Count : Journal of Accounting, Business and Management, 2025)
This study aims to deconstruct the classical supply and demand model by examining its theoretical inadequacy in explaining economic behavior within the rapidly evolving platform economy. While traditional microeconomic theory assumes transparent pricing, rational actors, and decentralized market mechanisms, digital platforms such as Uber, Amazon, and Airbnb introduce algorithmic pricing, behavioral engineering, and centralized control—fundamentally altering how markets operate. Employing a library research method, this study synthesizes literature from economics, platform studies, and digital labor research to build a multidisciplinary theoretical critique. The findings reveal that platform economies disrupt the core assumptions of classical models: supply becomes fluid and algorithmically mediated, while demand is shaped more by visibility, recommendations, and data-driven manipulation than price alone. The study also identifies a significant theoretical gap—existing models have not kept pace with the structural transformations driven by platform intermediation, network effects, and monopsonistic dynamics. The novelty of this research lies in its conceptual reframing of supply-demand interactions, proposing that platforms act not merely as intermediaries but as market-makers that actively design and control economic behavior. This reconceptualization provides a timely contribution to theoretical economics by offering a new lens to understand market dynamics in the digital age. The study concludes that a paradigm shift is necessary to align economic theory with the realities of platform-based interactions, which are increasingly dominant in global commerce and labor systems. Future research should continue bridging the gap between classical models and emerging digital economic structures.